MODAL SOSIAL PADA KOMUNITAS SUKU TORAJA DI PEKANBARU (STUDI IKATAN KERUKUNAN KELUARGA TORAJA (SANGTORAYAN) - Warni, Agus Sri; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The issues discussed in this thesis is the social capital in the Association of Family Harmony Toraja (Sangtorayan) and the efforts to maintain and strengthen social capital in the Association of Family Harmony Toraja (Sangtorayan). The subject of this study was 7 in which four core committee and three active members. Mechanical determination of informants in this research is by using purposive sampling technique. Purposive sampling is a technique of determining the informant to specific purposes only, where there is a tendency of researchers in selecting informants deemed informed and the problem in depth and can be trusted to be a source of data. The method used is qualitative research methods descriptive because this method explained in detail and depth of the issues examined. The theory used the theory of social capital consisting of the elements of trust, social networks and social norms proposed by Putnam. It can be concluded that social capital is very important in a group or organization, trust, social networks and the values and norms have a role in maintaining the relationship and continuity IKKT (Sangtorayan) in Pekanbaru who can be called a metropolitan city. Efforts to maintain and strengthen social capital in IKKT (Sangtorayan) in Pekanbaru is to uphold the values of unity and togetherness in IKKT (Sangtorayan). In maintaining a community or group is to increase social capital in which to build a network, increasing the confidence and discipline to the social norms that specify in an organization.Keyword : Community, Toraja, Social Capital